(untitled) (Revista Electrónica REDINE, 2022)
This essay expects to carry out an approach to the implications which derive from the academic reading practice in relation to the development of thinking in its different modalities: critical, reflexive, dialogical, complex, systemic, epistemic, and so on. So that, how the thinking gets to integrate, process, organize and structure the information and the reality in order to produce new interpretations. In summary, the academic reading is conceived as a transversal axis to the processes of teaching and learning in the university because it entails strategies, conventions and practices that allow to transcend higher levels of comprehension not only about scientific knowledge but about their own reality, sphere of activities in which s/he can operate competitively until accomplish their significant transformation.